Anti-caries effect of a novel elastic silicone appliance material incorporating sodium fluoride - Yu, Shuxing; Zhang, Lingyu; Ma, Qizhao; Zhou, Jing; Liu, Yaqi; Zou, Jing; Zhang, Qiong (Frontiers in Microbiology, 2025)
IntroductionThis study developed an elastic silicone appliance material incorporating sodium fluoride (NaF) and evaluated its mechanical properties, biocompatibility, antibacterial effects, and remineralization potential.MethodsSilicone components A and B were combined with varying concentrations of NaF (0.5, 1, 1.5, 2, and 2.5%), thoroughly mixed, and transferred into molds. After drying and curing, the resulting orthodontic appliance was retrieved from the mold and underwent finishing processes, followed by the assessment of its mechanical properties, cytotoxicity, and antibacterial impact. Additionally, the impact of this novel silicone appliance material on salivary biofilm’s activity and acid production was evaluated in samples from children with severe early childhood caries (S-ECC). The hardness of demineralized and remineralized bovine enamel was measured.ResultsIncorporating NaF (0.5, 1, and 1.5%) resulted in no cytotoxic effects, with cell viability >85%. The fluoride release rate initially increased over 14 days, followed by a gradual decline, maintaining a steady release for approximately 28 days. Incorporating 1.5% NaF preserved the mechanical properties and exhibited specific antibacterial properties that inhibited the growth, biofilm formation, and acid production activity of Streptococcus mutans (S. mutans) and saliva biofilms from S-ECC children. Furthermore, all concentrations of the samples helped improve enamel hardness loss.DiscussionThe novel silicone appliance material incorporating NaF exhibited antibacterial, fluoride releasing, and enamel remineralization properties while maintaining its physical and chemical integrity without cytotoxic effects.